Inovasi Digital untuk Meningkatkan Efisiensi Manajemen Keberlanjutan - Aris Priatno (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Digital innovation has become a crucial pillar in improving the efficiency of sustainability management across various industrial sectors. In this context, technologies such as artificial intelligence (AI), blockchain, and big data play a vital role in helping companies achieve their sustainability goals. This research aims to explore how digital innovation can be integrated into sustainability management strategies and identify the challenges faced in implementing it. Based on data analysis from various sources, it was found that companies that adopt digital technology tend to experience operational efficiency improvements of up to 30% and cost reductions of up to 20%. Furthermore, the use of blockchain technology in supply chain management has been shown to increase transparency and accountability, which are crucial in a sustainability context. Despite these benefits, challenges such as the lack of adequate technological infrastructure and digital literacy among stakeholders remain significant barriers. Therefore, Therefore, this study provides recommendations for increasing the adoption of digital innovation through education, intersectoral collaboration, and the development of supportive policies. With these steps, it is hoped that companies can maximize the potential of digital innovation to achieve greater sustainability.